2016
DOI: 10.1186/s13613-015-0102-8
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency and length of pediatric intensive care unit stay: a prospective observational study

Abstract: BackgroundDue to the limited data available in the pediatric population and lack of interventional studies to show that administration of vitamin D indeed improves clinical outcomes, opinion is still divided as to whether it is just an innocent bystander or a marker of severe disease. Our objective was therefore to estimate the prevalence of vitamin D deficiency in children admitted to intensive care unit (ICU) and to examine its association with duration of ICU stay and other key clinical outcomes.MethodsWe p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
46
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 29 publications
8
46
4
Order By: Relevance
“…In total, 23 patients in the VD group received anti-fungal treatment, which was markedly lower than the 42 patients from the placebo group (P = 0.02). .3) days] (P = 0.03), whereas cases of patient death were similar between the two groups (P = 0.22), which is consistent with previous studies reporting that vitamin D is not correlated with a higher prediction of risk mortality scores (18) but is with the duration of PICU stay (22) . Moreover, the length of central catheters was also significantly shorter in the VD group [3.1 (1.0) days] than the placebo group [4.3 (1.5) days] (P = 0.04).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In total, 23 patients in the VD group received anti-fungal treatment, which was markedly lower than the 42 patients from the placebo group (P = 0.02). .3) days] (P = 0.03), whereas cases of patient death were similar between the two groups (P = 0.22), which is consistent with previous studies reporting that vitamin D is not correlated with a higher prediction of risk mortality scores (18) but is with the duration of PICU stay (22) . Moreover, the length of central catheters was also significantly shorter in the VD group [3.1 (1.0) days] than the placebo group [4.3 (1.5) days] (P = 0.04).…”
Section: Resultssupporting
confidence: 89%
“…A low serum vitamin D level is also associated with higher incidence of lower tract acute respiratory infections (20) , the need for mechanical ventilation, increased vasopressor use and a lower serum calcium level in PICU (21) . In addition, it was reported that VDD children, with serum level of vitamin D metabolite 25-hydroxyvitamin D (25OHD) <20 ng mL À1 , had a longer duration of PICU stay than others (22) . Of particular interest to the present study, a recent in vitro antimicrobial screening study indicated that vitamin D exerted fungicidal functions against Candida albicans (23) .…”
Section: Introductionmentioning
confidence: 99%
“…There was no statistically significant difference between vitamin D level and PIM2 score. In accordance to our result, Sankar et al (24) and Rey et al (19) reported no significant relation between them. There was no statistically significant difference between vitamin D level on admission and length of PICU stay.…”
Section: Discussionsupporting
confidence: 82%
“…(23) In this context, we found that vitamin D levels were negatively correlated to PELOD score. Also, Sankar et al (24) observed that children who were vitamin D deficient at admission were more likely to have higher organ dysfunction scores, although the differences were not statistically significant. There was no statistically significant difference between vitamin D level and PIM2 score.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation